A Comparative Study of the Problem of Truth in Credit, with an Approach to Legal propositions, from the Western Philosophers and Ayatollah Javadi Amoli - mohammadhadi hazeri; ahmad vaezi (حکمت اسرا, 2018)
One of the important areas in the philosophy of law, and in the general sciences of credit, is the epistemology of propositions, meaning the question of the relation of these propositions to cognition and reason. Western philosophers are divided into naturalist and positivist groups, the first group of reason and the second group of the will of the state as the source of rights. For this reason, in the second group, the value of rules is rejected. With this background in mind, this article attempts to explain the epistemology of Islamic law by reflecting on Ayatollah Javadi Amoli's work. The findings are that Ayatollah Javadi Amoli is cognitive, believing that the basis of Islam's legal system is the will of the Shari'ah. The subjective origin and ultimate cause of this will is in accordance with human reality and perfection. These facts do not appear except in revelation and science devoid of ignorance, inadvertence, and adultery. Therefore, to discover those materials must be connected to revelation through reasoning or credible evidence, including reliable quotation. Therefore, it can be said that the source of the truth of the legal propositions and laws in Islamic law is al-Amari whose speech is revealed.